2004
DOI: 10.1111/j.1365-2966.2004.07508.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cluster mergers on arc statistics

Abstract: We study the impact of merger events on the strong lensing properties of galaxy clusters. Previous lensing simulations were not able to resolve dynamical time-scales of cluster lenses, which arise on time-scales that are of the order of a Gyr. In this case study, we first describe qualitatively with an analytic model how some of the lensing properties of clusters are expected to change during merging events. We then analyse a numerically-simulated lens model for the variation in its efficiency for producing bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(142 citation statements)
references
References 50 publications
7
135
0
Order By: Relevance
“…This seems to suggest that some cluster property rather than the mass plays an important role for boosting the lensing cross sections of these small lenses, which also influences their X-ray luminosity. As discussed in Torri et al (2004) and in Fedeli & Bartelmann (2007), mergers are likely to explain the effect we observe here.…”
Section: X-ray Luminositiesmentioning
confidence: 63%
See 2 more Smart Citations
“…This seems to suggest that some cluster property rather than the mass plays an important role for boosting the lensing cross sections of these small lenses, which also influences their X-ray luminosity. As discussed in Torri et al (2004) and in Fedeli & Bartelmann (2007), mergers are likely to explain the effect we observe here.…”
Section: X-ray Luminositiesmentioning
confidence: 63%
“…As discussed in Torri et al (2004), the shear produced by the substructures enhance the ability of the clusters to produce strong lensing, because it makes critical even those lenses where the convergence is not enough to ensure it (Îș ≄ 1 at some point).…”
Section: Halo Triaxiality and Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…5.2, for summaries), and references therein). In particular, Torri et al (2004) analysed numerically simulated mergers of galaxy clusters. These authors found that mergers substantially change the shape of the critical curves and can boost a cluster's efficiency to produce giant arcs by an order of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the curves exhibit strong peaks which are connected to merger events arising in single clusters. It has been recently shown that during such events, which occur on timescales of some Gyr, the cluster efficiency for strong lensing is strongly enhanced (Torri et al, 2004), due to the combined effect of the increasing shear and convergence. It is interesting to note that, by comparing the cross sections as function of redshift for different cosmological models, there is a correspondence between the number of the peaks in the curves.…”
Section: Lensing Cross Sectionmentioning
confidence: 99%